Evolutionary economic geography and its application in regional researc - Zakrzewska-Półtorak, Alicja (Ewolucyjna geografia ekonomiczna i jej zastosowanie w badaniach regionalnych, 2014)
Evolutionary economic geography became popular in the late 1990s. The study has developed on the basis of evolutionary economics, which has achieved greater success in explaining phenomena in the microeconomic than in the macroeconomic sphere and it has had non-spatial character. Evolutionary economic geography is an alternative in economic geography and regional planning for static or pseudo-dynamic research. Supporters of evolutionary economic geography, by criticizing among others New Economic Geography by P. Krugman, conduct research with the use of generalized Darwinism, path dependence and complexity theory. In this paper the author discusses the basic approach and assumptions of evolutionary economic geography and its application in regional economy, especially as an answer to the search for ways out of the economic crisis of regions and cities
Biblioteka Regionalisty, 2014, Nr 14, s. 91-98
Keywords: evolutionary approach; regional economy; path dependence; regional resilience; podejście ewolucyjne; gospodarka regionalna; zależność od ścieżki; prężność regionalna